Conditional Cash Transfers and Education Quality in the Presence of Credit Constraints - Del Rey, Elena; Estevan, Fernanda (Université d'Ottawa | University of Ottawa, 2011)
We investigate the relative merits of unconditional cash transfers (UCT), conditional cash transfers (CCT), and improvements in education quality on efficiency and welfare. In our setting some parents under-invest in their children's education because capital market imperfections prevent them from borrowing. When credit constrained households can be perfectly targeted by the government, we show that CCT are more effective than UCT in enhancing efficiency and equivalent in terms of welfare. When public education quality is very low, raising quality is welfare improving, but is never efficiency enhancing. If the government cannot target constrained households, UCT may be the best policy both in terms of efficiency and welfare. / Nous étudions les avantages relatifs des transferts monétaires inconditionnels (UCT), des transferts monétaires conditionnels (CCT) et de l’amélioration de la qualité de l'éducation sur l'efficacité et le bien-être. Dans notre modèle, certains parents sous-investissent dans l'éducation de leurs enfants parce que des imperfections du marché de crédit les empêchent d'emprunter. Lorsque les ménages confrontés à des restrictions du crédit peuvent être parfaitement ciblés par le gouvernement, nous montrons que les CCT ont un impact plus important en termes d’efficacité que les UCT et sont équivalents en termes de bien-être. Lorsque la qualité de l'éducation est très faible, l'amélioration de la qualité augmente le bien-être mais ne peut pas améliorer l'efficacité. Si le gouvernement ne peut pas cibler les ménages contraints monétairement, les UCT peuvent être la meilleure politique à la fois en termes d'efficacité et de bien-être.
Keywords: conditional cash transfers; public education; education quality; unconditional cash transfers; credit constraint; efficiency; welfare; transferts mone?taires conditionnels; e?ducation publique; qualite? de l’e?ducation; transferts mone?taires inconditionnels; restrictions du cre?dit; efficacite?; bien-e?tre